Bleeding risk prediction in elderly patients managed invasively for Acute Coronary Syndromes: external validation of the PRECISE-DAPT and PARIS risk scores. (25th November 2020) - Montalto, C; Crimi, G; Morici, N; Piatti, L; Grosseto, D; Sganzerla, P; Tortorella, G; De Rosa, R; De Luca, L; De Luca, G; Palmerini, T; Valgimigli, M; et al.
Abstract: Background: Tailoring Dual Antiplatelet Therapy (DAPT) to each patient bleeding and ischemic risk profile is a majopr challenge in everyday clinical practice. As the elderlies were underrepresented in validation cohorts of bleeding risk scores, their generalizability in this context is uncertain. Purpose: We sought to assess the clinical utility of the PRECISE-DAPT and PARIS bleeding risk scores to elderly patients suffering from ACS and undergoing invasive management. Methods: Our external validation cohort included 1, 883 patients older >74 years admitted for ACS and treated with PCI from 3 multicenter, randomized trials. Bleeding risk scores were calculated on a patient-level and subjects were stratified into risk categories according to each risk score definition. Results: After a median follow-up of 365 days, patients in the high-risk categories according to the PRECISE-DAPT score experienced a higher rate of BARC 3–5 bleedings (log rank p=0.002) while this was not observed for those in the high-risk category according to the PARIS risk score (log rank p=0.3). Both scores had a moderate discriminative power (c-statistics 0.70 and 0.64, respectively) and calibration was accurate for both risk scores (all χ 2 >0.05), but PARIS risk score was associated to a greater overestimation of the risk (mean D observed-predicted probability = −0.65 for PRECISE DAPT and −4.62 for PARIS, p=0.02; Figure 1). Decision curve analysis was in favor of the PRECISE-DAPT score up to a risk threshold of 2%. A sensitivity showed that calibration and discrimination power was moderate for both risk scores also after including BARC 2 events. Conclusion: In the setting of older adults managed invasively for ACS both the PARIS and the PRECISE-DAPT scores were moderately accurate in predicting bleeding risk. However, the use of the PRECISE-DAPT is associated with better performance and a higher net benefit. Funding Acknowledgement: Type of funding source: None